MITIGATING SPEAKING ANXIETY THROUGH SUPPORTIVE TEACHER EVALUATIVE DISCOURSE IN ESP EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Speaking anxiety is one of the most common psychological challenges experienced by students in English for Specific Purposes (ESP) classrooms. Among philology undergraduates, anxiety during oral communication often negatively affects participation, fluency, confidence, and academic performance. Teacher evaluative discourse plays a significant role in either intensifying or reducing these emotional difficulties. The present study investigates how supportive teacher evaluative discourse can mitigate speaking anxiety among philology undergraduates in ESP education. Using a qualitative research methodology, the study collected data through classroom observations and semi-structured interviews conducted with undergraduate ESP students. The findings reveal that supportive feedback strategies, emotionally sensitive correction methods, and psychologically safe classroom environments significantly reduce students’ fear of negative evaluation and improve communicative confidence. Conversely, harsh criticism and public correction contribute to communication avoidance and professional face-threat. The article emphasizes the importance of empathetic teacher-student interaction and student-centered feedback practices in promoting effective oral communication and emotional well-being in ESP classrooms.
Keywords: speaking anxiety, ESP education, evaluative discourse, supportive feedback, professional face-threat, philology undergraduates, classroom interaction